Epilogue: User and Used: Psychoanalytic Observations on Relentless Technological Innovation and the Human Being. - Shulman, Michael E. (Psychoanalytic Inquiry, 2023)
Capitalism and the development of technology are inextricably interlinked, from capitalism's origins. In the name of the "reality principle", psychoanalysts may throw up their hands in the face of the juggernauts of technology and capitalism, avoiding examination of the exploitative and extractive elements of technology as much as they avoid examining those of capitalism. However, as a piece of technology, the smartphone and other internet-connected devices become extensions not only of the self outward, but extensions of technology and the interests of the businesses that develop them inward into the self. Yet most of us, at least most adult Americans, including most adult American psychoanalysts, are so resigned to technological advance, as well as to the acceptance of ubiquitous use of technology, in the name of a prosperous economy ("well, that's just the way it is, that's how capitalism works"), that they are rendered spectators to the infiltration of technology into our existences.